Faktor-faktor Penyebab Kecelakaan Kerja di Areal Penambangan Batu Kapur pada Pt. Sumbar Calcium Pratama - Rezki Hidayat; Rijal Abdullah; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2018)
At PT. Sumbar Calcium Pratama found several violations against existingSOP. There are still many workers who work in hazardous work positions, the useof equipment and machines in an unsafe way and they not use the protection toolsthat have been provided by the company. The purpose of this research is to revealthe factors that cause work accidents, reveal the most dominant factors as thecause of occupational accidents, reveal the potential hazards that can causeaccidents, can calculate the percentage of the frequency and severity of workaccidents, can cause human error or unsafe employee behavior, and can give anidea of the use of hazard card.In this research, combined between theory with field data, so get problemsolving approach. And the results of data processing will be analyzed forsubsequent to be generated a recommendation.Based on the results of research conducted can be summed up some of thefollowing. First, accident-causing factors are generally caused by unsafe andunsafe measures, the most dominant factor is unsafe, other potential hazards thatallow the occurrence of accidents in the implementation of mining activities inPT. Sumbar Calcium Pratama, such as the convetional mining, in 2016, 87.3%frequency rate and severity rate of 43.69%, and the results of the questionnairenote that the attitude and application of employees are in fairly good category.Keywords: K3, unsafe action, unsafe condition